(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Childhood infection is often caused by otitis media (OM), with around 60% of children experiencing a minimum of a single episode at the age of 4. Objective: This study determined and analysed clinical outcomes of otitis media as well as assessed risk factors for children. Patients and methods: We recruited 76 children aged between 3-14 years, and their data was collected from Azadi Teaching Hospital in Kirkuk, Iraq, for a period extending from January 7, 2023, until September 15, 2024. This data included both the most common symptoms in children with otitis media and the severity classification. Otitis media, which included acute otitis media, otitis media with effusion, and chronic otitis media. Moreover, this study recorded clinical data on pediatric patients after taking treatment with amoxicillin in terms of rates of pain, complications, recovery time, quality of life, severity of symptoms, and identification of risk factors affecting pediatric patients after the treatment period. Results: This study recorded clinical parameters in terms of diagnosis, treatment, and outcomes, which included females being a risk factor in 48 cases, more than males (28 cases), exposure to passive smoking, which included 50 cases, and family history of ear infections, which included 23 cases. We classified the otitis media severity measures. They are acute (50 cases), effusion (only 3 cases), and chronic (23 cases). Children commonly experience fever in 70 cases, ear pain in 63 cases, decreased appetite in 18 cases, and bacterial infection in 76 cases. All children also received treatment with amoxicillin. For a period of 5 days or more, complications included nausea and vomiting in 3 cases, allergies in 2 cases, and hearing loss in only 2 cases. Quality of life standards were determined for patients, as the criteria included both ear symptoms: 18.95 ± 4.87 before treatment with amoxicillin and 47.72 ± 6.33 after treatment with amoxicillin. Hearing function was 28.21±3.96 before amoxicillin treatment and 51.74±2.68 after amoxicillin treatment. Conclusion: Amoxicillin treatment is the best, most preferred, and most effective treatment for treating bacterial infections in patients who have middle ear infections, which causes a lower rate of complications, a lower rate of pain, and a better and faster recovery rate.